2018
DOI: 10.15570/actaapa.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) infection and vaccination: knowledge and attitudes among healthcare professionals and the general public in Slovenia

Abstract: This study evaluated the range of concerns among various groups of healthcare professionals and the general public regarding the timing of HPV vaccination, its safety and adverse effects, the impact of HPV vaccination on sexual behavior, and the importance of vaccinating boys. Methods The study was designed to obtain information about the knowledge of and attitudes toward HPV infection and vaccination among various healthcare professionals and the general public. For participants that attended lectures on HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
1
13
1
5
Order By: Relevance
“…However, in our study, we could not find differences in terms of level of HPV-related knowledge between residents and specialists/doctors as well as among gynecologists, pediatricians, and internal medicine doctors (except for the first subset of items of the third part of the questionnaire), whereas some scholars have reported differences, with the highest level of knowledge of and belief in the anti-HPV vaccine, its effectiveness, and its safety being observed among pediatricians and school medicine specialists [33]. On the other hand, a study conducted in Louisiana, United States failed to find a significant association between knowledge strength and levels and years in practice or practice type [34].…”
Section: Discussioncontrasting
confidence: 69%
“…However, in our study, we could not find differences in terms of level of HPV-related knowledge between residents and specialists/doctors as well as among gynecologists, pediatricians, and internal medicine doctors (except for the first subset of items of the third part of the questionnaire), whereas some scholars have reported differences, with the highest level of knowledge of and belief in the anti-HPV vaccine, its effectiveness, and its safety being observed among pediatricians and school medicine specialists [33]. On the other hand, a study conducted in Louisiana, United States failed to find a significant association between knowledge strength and levels and years in practice or practice type [34].…”
Section: Discussioncontrasting
confidence: 69%
“…This is a substantial change from previously reported results that the media is a "poor source of comprehensive information on cervical cancer" [41]. Two separate pieces of research from Hungary and Slovenia also found that the media, namely the internet and magazines, to be dominant sources of information about this topic [32,33,42]. This confirms that the media has a great impact on public opinion and thus can be a powerful tool for increasing the awareness of CC.…”
Section: Discussionmentioning
confidence: 54%
“…In Slovenia, HPV vaccination became the first non-mandatory vaccine to be included in the national vaccination program in the 2009/2010 school year (Troha, Šterbenc, Mlaker, & Poljak, 2018). Routine vaccination is for girls aged 11 or12 years whereas boys are not included in the program.…”
Section: Vaccination Against Hpvmentioning
confidence: 99%